PENGARUH STRES KERJA DAN KONFLIK KERJATERHADAP KINERJA KARYAWAN KONVEKSI TAS MY CLOSET MALANG (Studi KasusPadaSeluruhKaryawanKonveksi My Closet Malang) - Alfina Yostika; Hadi Sunaryo; Muhammad Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2017)
AbstractThis study aims to determine the effect of work stress variables and work conflicts on employee performance of My Closet Bag Complex. In this study, the population is all employees of My Closet Bag Convection Malang amounting to 35 people. Sampling in this study using census method that is the entire amount of population subject to sample population, so that the sample of this study amounted to 35 people. The method used in this study is the method of quantitative analysis. The media used is media questionnaire (questionnaire). The results of this study indicate that between the variables of work stress and work conflict significantly there are some that affect the performance of employees Convection Bag My Closet Malang, while partially, the test results show that job stress does not significantly affect employee performance (sig 0.00), conflict Work has a significant effect on employee performance (sig 0.037).Keywords : work stress variable, work conflict and employee performance.